Equine infection with Leishmania spp. in Costa Rica: Study of five cases. Issue 6 (2nd August 2021) - Ortega‐García, María Victoria; Salguero, Francisco Javier; García, Nerea; Domínguez, Mercedes; Moreno, Inmaculada; Berrocal, Alexis
Abstract: Background: Cutaneous forms of leishmaniosis due to Leishmania braziliensis have been reported in horses in the New World. Domestic animals play a role in the transmission of the disease. In Costa Rica, human cases of L. braziliensis, L. panamensis and L. infantum have been reported. Objectives: The present report describes five cases of equine cutaneous leishmaniosis in Costa Rica. The aetiological diagnosis was based on the presence of the parasite within the lesions. Methods: Skin biopsies were used to perform histopathological analyses of the lesions. Immunohistochemistry was used to detect the presence of the Leishmania spp . antigens in tissue sections. Laser‐capture micro‐dissection and quantitative real‐time PCR techniques were carried out to detect the pathogen nucleic acid within the microscopic lesions. Results: Histopathological analyses showed a granulomatous inflammation within the dermis, with multi‐nucleated giant cells, macrophages, lymphocytes and few neutrophils and eosinophils. We detected the parasite by immunohistochemistry, using a rabbit polyclonal antibody raised against Leishmania spp . However, we could not identify Leishmania spp . by quantitative real‐time PCR in formalin‐fixed paraffin‐embedded tissues, using specific primers for the conserved region in the minicircle of the Leishmania DNA kinetoplast. Conclusions: Our results emphasise the importance of Leishmania spp . not only as a causative agent of equine cutaneous disease in the New World, but also as a possible emerging pathogen. Leishmaniosis is one of the most prevalent parasitic public health problems worldwide, and equines may have a role in the epidemiology of the disease. Abstract : The present report describes 5 cases of equine cutaneous leishmaniosis in Costa Rica using histopathology, immunohistochemistry and qPCR. Our results emphasise the importance of Leishmania spp. not only as a causative agent of equine cutaneous disease in the New World but also as a possible emerging pathogen. Leishmaniosis is one of the most prevalent parasitic public health problems worldwide, and equines may have a role in the epidemiology of the disease.